Effects and mechanisms of iron overload on the proliferation and differentiation of preosteoblastic cells via a 3D microsphere culture system - Pan, Yu; Luo, Xiaojing; Zhao, Renfeng; Zhang, Chengdong; Luo, Xuwei; Feng, Gang; Xiao, Dongqin (Frontiers in Bioengineering and Biotechnology, 2026)
BackgroundIron overload-related osteoporosis has garnered significant attention, yet its pathological mechanisms remain unclear. Traditional two-dimensional (2D) culture systems often fail to recapitulate the extracellular matrix (ECM) microenvironment, leading to discrepancies between in vitro and in vivo findings.MethodsWe developed a three-dimensional (3D) culture system using methacrylated gelatin (GelMA) microspheres to culture preosteoblastic cells, simulate the bone microenvironment under iron overload conditions, and systematically examine changes in cellular morphology, viability, function, and gene expression.ResultsIron overload impaired cell viability, induced oxidative stress, and inhibited osteogenesis in both 2D and 3D cultures. However, cells in 3D exhibited enhanced resilience, including reduced ROS levels, higher viability, preserved cytoskeletal integrity, and less apoptosis and G1-phase arrest. Compared to 2D, 3D-cultured cells showed downregulated expression of ITGA1 and ITGB1, decreased adhesion function, and promoted proliferation. Transcriptomics further revealed activation of NF-κB signaling and DNA replication pathways in 3D, while key pathways such as Hippo, focal adhesion, and Wnt were suppressed.DiscussionThe GelMA microsphere-based 3D system provides a physiologically relevant model for studying iron overload. These findings offer not only mechanistic insights but also suggest potential microenvironment-targeted therapeutic strategies for iron overload-associated osteoporosis.